Faktor yang Mempengaruhi Penjualan UMKM Kuliner (Studi Kasus pada “Pecel Cik Meri 99” di Kecamatan Metro Pusat, Kota Metro, Provinsi Lampung) - Daud, Syahril; Dhani, Akhmad; Hartono, Celine Viona; Tarigan, Natalia Karolina (Jurnal EMT KITA, 2025)
MSMEs play a vital part in the Indonesian economy, especially MSME Pecel Cik Meri 99, which is experiencing sales issues. To compete, MSMEs must evaluate several key variables, including product, price, location, and advertising. This study takes a quantitative approach, focussing on visitors to MSME Pecel Cik Meri 99. Because the population is unknown, the sample size is determined using the Lemeshow formula. According to the study's findings, product, price, and location had no substantial impact on sales volume. On the contrary, promotion has a favourable and considerable effect on sales, and product, price, location, and promotion all have an impact on sales at Warung Pecel Cik Meri 99.